Firing Patterns of Human Biceps Brachii Motor Units During Isotorque Ramp-and-Hold Movements in the Elbow Joint - Tal’nov, A.N.; Tomiak, T.; Maznychenko, A.V.; Dovgalets, G.V.; Kostyukov, A.I. (Нейрофизиология, 2014)
The activity of 18 motor units (MUs) of m. biceps brachii was studied in four adults during high-amplitude isotorque ramp-and-hold movements in the elbow joint. The recorded MUs had low isometric thresholds (below 6% of maximal voluntary contraction). During the examined movement, MUs of group I responded to application of subthreshold loads by increases in their firing rates, MUs of group II reacted to suprathreshold loads by decreases in the attained activity level, and background firing of MUs of group III at application of suprathreshold loads did not change. Dependences between the joint angle and firing rate, as well as between the velocities of these parameters, were positive in group I MUs and negative in those of group II. A decrease in the firing rate of MUs during flexion movements is likely to be related to nonlinear effects during the torque generation by the elbow flexors due to the specificity of geometrical arrangement of MU fibers with respect to the joint.